2021
DOI: 10.3329/dujbs.v30i1.51808
|View full text |Cite
|
Sign up to set email alerts
|

Effects of poultry litter compost and chemical fertilizers on growth and yield of field grown sunflower (Helianthus annus L.)

Abstract: A field experiment was carried out in the research farm of Charfasson Govt. College, Bhola during Rabi season in 2016-2017 to evaluate the effects of poultry litter (PL) compost and NPK fertilizers on growth and yield of sunflower cv. BARI-2 (Keroni-2). Sixteen treatments were used with three replications each. Treatments were T1 : Control (-PL and –NPK), T2 : 1.5 ton PL/ha, T3 : 3.0 ton PL/ha, T4 : 4.5 ton PL/ha, T5 : N40P30K50 kg/ha, T6 : N80P60K100 kg/ha, T7 : N120P90K150 kg/ha, T8 : 1.5ton PL/ha + N40P30K5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Significantly the highest total fruit dry matter (76.91 g plant -1 ) was measured at treatment T 5 (20t VC ha -1 ) followed by T 6 and T 4 (statistically identical) and the lowest total fruit dry matter (25.14 g plant -1 ) was counted under control treatment T 1 , respectively. Alauddin et al (2021) reported that the application of organic manure significantly increased dry matter production plant -1 of sunflower. The total dry mass and fruit dry mass ratios differed significantly among treatments, while the highest ratio (7.35) was observed at T 5 (20t VC ha -1 ), followed by T 4 (6.42) and the lowest was seen under treatment T 2 (3.02; 5t VC ha -1 ).…”
Section: Dry Biomass Of Plant Parts and Fruits And Their Ratiosmentioning
confidence: 99%
“…Significantly the highest total fruit dry matter (76.91 g plant -1 ) was measured at treatment T 5 (20t VC ha -1 ) followed by T 6 and T 4 (statistically identical) and the lowest total fruit dry matter (25.14 g plant -1 ) was counted under control treatment T 1 , respectively. Alauddin et al (2021) reported that the application of organic manure significantly increased dry matter production plant -1 of sunflower. The total dry mass and fruit dry mass ratios differed significantly among treatments, while the highest ratio (7.35) was observed at T 5 (20t VC ha -1 ), followed by T 4 (6.42) and the lowest was seen under treatment T 2 (3.02; 5t VC ha -1 ).…”
Section: Dry Biomass Of Plant Parts and Fruits And Their Ratiosmentioning
confidence: 99%
“…Application of organic manures singly or in combination with either other organic fertilizers or chemical fertilizers have been proved effective to enhance growth and yield of various plants like Sunflower, Soybean, Okra, Gynura, Ground nut (Alauddin et al 2019). The increasing cost of chemical fertilizers and their harmful effects on the soil health are also an important consideration for the use of organic nutrients (Patel et al 2005).…”
Section: Introductionmentioning
confidence: 99%